2013
DOI: 10.1103/physrevlett.111.234101
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Synchronization of Quantum van der Pol Oscillators with Trapped Ions

Abstract: The van der Pol oscillator is the prototypical self-sustained oscillator and has been used to model nonlinear behavior in biological and other classical processes. We investigate how quantum fluctuations affect phase locking of one or many van der Pol oscillators. We find that phase locking is much more robust in the quantum model than in the equivalent classical model. Trapped-ion experiments are ideally suited to simulate van der Pol oscillators in the quantum regime via sideband heating and cooling of motio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
407
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 279 publications
(419 citation statements)
references
References 56 publications
10
407
0
2
Order By: Relevance
“…Indeed, comparisons of numerical calculations using the full master equation showed that the Fokker-Planck equation substantially underestimated the strength of the features which emerge in the relative phase distribution in the quantum regime. Interestingly, a very similar underestimate of synchronization effects was obtained using a semiclassical model for the case of two van der Pol oscillators [7]. In our case, it seems that low photon occupation number is the key factor that leads to differences between quantum and semiclassical predictions.…”
Section: Conclusion and Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…Indeed, comparisons of numerical calculations using the full master equation showed that the Fokker-Planck equation substantially underestimated the strength of the features which emerge in the relative phase distribution in the quantum regime. Interestingly, a very similar underestimate of synchronization effects was obtained using a semiclassical model for the case of two van der Pol oscillators [7]. In our case, it seems that low photon occupation number is the key factor that leads to differences between quantum and semiclassical predictions.…”
Section: Conclusion and Discussionsupporting
confidence: 55%
“…Recent theoretical work has explored different ways of quantifying synchronization in quantum oscillators [5,7,14,15,20], as well as investigating the connection between it and measures of correlation such as mutual information and entanglement [5,8,10,15,19]. Detailed comparisons have also been made between the predictions of quantum models and those of related semiclassical or classical descriptions [7,12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Initially, given the usual nature (scale) of the systems in which synchronization is typically observed, it seems superfluous thinking of a quantum theory for the Kuramoto model. However, there is not doubt about the fundamental importance of studying quantum fluctuations within the emergence of synchronized states [9][10][11][12][13][14][15][16]. Moreover, the Kuramoto model has been implemented on circuits and microand nanomechanical structures [17,18], systems that have already met the quantum domain [19,20].…”
Section: Introductionmentioning
confidence: 99%